Menjaga Integritas Dan Profesionalisme: Tinjauan Kode Etik Profesi Hukum Dalam Praktik Sehari-Hari - Erleni, Erleni; Siallagan, Yonatal (Sekolah Tinggi Ilmu Hukum Sumpah Pemuda, 2024)
The study aims to determine how important the code of ethics of the legal profession is, in Indonesia, and how the application of the code can improve the quality of legal services and increase public confidence in the legal system. The purpose of the Code of Ethics is to ensure that legal practice is conducted with integrity, honesty, and responsibility, as well as to protect the public interest and preserve the dignity of the law profession. In addition, the study examines the problem and the efforts made to solve it. The research uses a qualitative approach by looking at literature, regulations, and case studies related to the code of ethics of the legal profession. According to the research, although the law profession has good codes, they often face problems such as lack of supervision, lack of ethical awareness of practitioners, and external pressure that affects professional decisions. This study shows that sustained ethical education, more surveillance, and firm sanctions for violations of the code of ethics are crucial.Thus, the integrity and professionalism of legal practice can be enhanced and public confidence in the legal system can be preserved.